2007
DOI: 10.1097/01.anes.0000265422.07864.37
|View full text |Cite
|
Sign up to set email alerts
|

Volume Replacement Therapy during Major Orthopedic Surgery Using Voluven® (Hydroxyethyl Starch 130/0.4) or Hetastarch

Abstract: Voluven (HES 130/0.4) and hetastarch are equally efficacious plasma volume substitutes; however, HES 130/0.4 has a lesser effect on coagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 31 publications
1
56
0
2
Order By: Relevance
“…The hemodilution effect of HES 130/0.4 associated with its mode of action was reflected by significant changes in hematological and coagulation parameters. The quick recovery of Factor VIII and vWF in adults after surgery is in line with other findings [3,11,12]. However, it is not possible to separate the effects of profound bleeding from those attributable to hemodilution in an uncontrolled trial.…”
Section: In Patients Undergoingsupporting
confidence: 78%
See 1 more Smart Citation
“…The hemodilution effect of HES 130/0.4 associated with its mode of action was reflected by significant changes in hematological and coagulation parameters. The quick recovery of Factor VIII and vWF in adults after surgery is in line with other findings [3,11,12]. However, it is not possible to separate the effects of profound bleeding from those attributable to hemodilution in an uncontrolled trial.…”
Section: In Patients Undergoingsupporting
confidence: 78%
“…They concluded that the hemodynamic effects of 6% HES 130/0.4 were at least similar to 5% human albumin. Langeron et al (2001) [11] and Gandhi et al (2007) [12] could demonstrate equivalence of 6% HES 130/0.4 with 6% HES 200/0.5 or 6% HES 450/0.7 in volume needed to restore or maintain hemodynamics during orthopedic surgery. Vogt et al (1996) [13] compared 6% HES 200/0.5 with 5% human albumin and demonstrated similar volume needs to stabilize hemodynamics.…”
Section: In Patients Undergoingmentioning
confidence: 97%
“…Hydroxyethyl substitution causes the solubility of starch to increase and delays hydrolysis, thus delaying the degradation of starch molecules and excretion. 11 HES is excreted by the kidneys and the rate of decomposition of starch is based on the molar substitution and C2/C6 ratio, which is the substitution of hydroxyethyl at the C2 or C6 location. The higher the molar substitution and C2/C6 ratios, the slower the decomposition, ultimately leading to plasma accumulation.…”
Section: 10mentioning
confidence: 99%
“…However, the problem seems to be associated more with the higher substituted HES that have medium to high MW. 11 An increasing number of prospective studies have compared Voluven with other starches ( Table 2).…”
Section: 10mentioning
confidence: 99%
“…2,6 In contrast to the earlier hydroxyethyl starch (HES) solutions, which had a large molecular weight and a high degree of substitution, the new lower molecular weight HES solutions with a lower degree of substitution, such as HES 130/0.4, have shown a favourable pharmacological profile with fewer side effects. [7][8][9][10][11][12][13] Best known for their use as intravascular volume expanders, HES solutions are also associated with microcirculatory improvement and antiinflammatory properties. [14][15][16][17][18] Despite their adverse effects in other settings, namely, on renal function, coagulation, and tissue storage, it was suggested previously that the older high molecular weight HES can reduce the deleterious effect of IRI.…”
Section: Résumémentioning
confidence: 99%